Discovery, pharmacology, and clinical profile of omadacycline, a novel aminomethylcycline antibiotic. Issue 24 (15th December 2016) - Tanaka, S. Ken; Steenbergen, Judith; Villano, Stephen
Graphical abstract: Abstract: Omadacycline is novel, aminomethyl tetracycline antibiotic being developed for oral and intravenous (IV) administration for the treatment of community-acquired bacterial infections. Omadacycline is characterized by an aminomethyl substituent at the C9 position of the core 6-member ring. Modifications at this position result in an improved spectrum of antimicrobial activity by overcoming resistance known to affect older generation tetracyclines via ribosomal protection proteins and efflux pump mechanisms. In vitro, omadacycline has activity against Gram-positive and Gram-negative aerobes, anaerobes, and atypical pathogens including Legionella and Chlamydia spp. Omadacycline offers once daily oral and IV dosing and a clinical tolerability and safety profile that compares favorably with contemporary antibiotics used across serious community-acquired infections where resistance has rendered many less effective. In studies in patients with complicated skin and skin structure infections, including those with MRSA infections, omadacycline exhibited an efficacy and tolerability profile that was comparable to linezolid. Ongoing and planned clinical studies are evaluating omadacycline as monotherapy for treating serious community-acquired bacterial infections including Acute Bacterial Skin and Skin Structure Infections (ABSSSI) and Community-Acquired Bacterial Pneumonia (CABP). This review provides an overview of the discovery, microbiology, nonclinical data, and available clinical safety and efficacy data for omadacycline, with reference to other contemporary tetracycline-derived antibiotics.